User Personas: Discovering Factors That Influence Genz’s Sedentary Lifestyle for the Development of a Mobile Exergame Design Model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of mobile devices for youths in tertiary education is found to be linked to sedentary behaviour. This paper attempts to create user personas on these youths and finding the factors that affect their sedentary lifestyles, which could assist the development of a mobile exergame design model. An online survey consisting of sociodemographic and IPAQ questionnaires was used to collect data on students in a public university. Three user personas were derived, which are based on their weekly physical activity levels: Low, Moderate, and High. It was found that income status, time management, daily smartphone usage, and fitness self-rating has a direct relationship with physical activity levels. The user personas share a common factor in that smartphone usage is essential to manage the youths’ daily activities regardless of their physical activities. The derived user personas would assist future mobile exergame design model development by concentrating on the influencing factors from the Low and Moderate physical activity level groups.